Efforts to Implement Reflective Journals as a Form of MI Teacher Professionalism - Putri, Fia Alifah; Setiawati , Eka; Indrawati; Parid, Miptah; Taufiqurrahman, Safikri (International Journal of Education, Language, and Social Science, 2023)
This research presents a practical model for integrating reflective journals into the professional development of Madrasah Ibtidaiyah  (MI) teachers. Utilizing a descriptive qualitative design, the study involved data collection, presentation, reduction, and drawing conclusions. The findings reveal that reflective journals, in alignment with the Tanoto Foundation's theory, support three key aspects: (1) Description, allowing MI teacher candidates to collectively document experiences, enhance time management, identify opportunities for applying theoretical knowledge, and cultivate a passion for research; (2) Evaluation, encouraging the assessment of cognitive, affective, and psychomotor aspects, the selection of evaluation techniques, the establishment of benchmarks, norms, or criteria for learning assessment, and data collection; and (3) Future planning, emphasizing patterns for time and class management. The study advocates for a shift toward more dynamic time management patterns and underscores the importance of responsive teaching strategies to address the diverse learning needs of students.